TeamBridge 2.0: an extensible and non-invasive middleware for control and adapting games for motor rehabilitation - Dantas, Rummenigge; Alves, Alan K. S.; dos Santos, Andre V. (Journal on Interactive Systems, 2024)
This work present the TeamBridge 2.0, a middleware able to perform the communication between digital games and hardware devices, like joysticks, mice and cameras (both rgbd and monocular). That communication does not require any modification to the game source code, allowing an old game to be adapted to work with a new hardware device. To prove this, tests were carried out with several games, including one of them being a commercial game. This middleware also allows the use of more than one device at the same time, so we can obtain more accurate information, one device can supply the deficiencies of the other. Finally, we performed tests to make sure that the middleware would not interfere with the user experience. Tests have shown that TeamBridge 2.0 can receive, interpret and send information quickly, the time varies according to the device used, getting 33ms when used with Kinect, 40ms with Leap Motion and 255ms with a DIY Data-Glove.